2022
DOI: 10.3389/fsurg.2022.983931
|View full text |Cite
|
Sign up to set email alerts
|

Sex and gender determinants following spinal fusion surgery: A systematic review of clinical data

Abstract: In the last decade, numerous studies analyzed and described the surgical outcomes in male and female patients submitted to orthopedic surgery. Although this, the impact of sex/gender on spinal fusion surgery clinical outcomes is still poorly defined. This review systematically maps and synthesizes the scientific literature on sex/gender differences in postoperative outcomes for patients undergoing spinal fusion surgery. The search was performed in PubMed, Scopus, and Web of Science in the last 22 years. Clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 62 publications
2
3
0
Order By: Relevance
“…It is also noteworthy that postoperative outcomes, including pain, are reportedly worse in women than in men after spine surgery. 31 This aligns with our results suggesting that spine surgery induces greater central sensitization in females than in males. Future studies are warranted to determine whether females and males develop central sensitization after spine surgery in a mechanistically different manner, and if so, whether it is the basis of the sex differences in the pain-related outcomes of spine surgery and the efficacy of SCS.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is also noteworthy that postoperative outcomes, including pain, are reportedly worse in women than in men after spine surgery. 31 This aligns with our results suggesting that spine surgery induces greater central sensitization in females than in males. Future studies are warranted to determine whether females and males develop central sensitization after spine surgery in a mechanistically different manner, and if so, whether it is the basis of the sex differences in the pain-related outcomes of spine surgery and the efficacy of SCS.…”
Section: Discussionsupporting
confidence: 92%
“…Our results support the clinical report, showing that SCS-treated female mice were still more hypersensitive to von Frey filament stimulation of their hind paws than their male counterpart. It is also noteworthy that postoperative outcomes, including pain, are reportedly worse in women than in men after spine surgery 31. This aligns with our results suggesting that spine surgery induces greater central sensitization in females than in males.…”
Section: Discussionsupporting
confidence: 91%
“…Salamanna et al analyzed in a review the studies considering sex-and gender-related differences in patients treated for lumbar degenerative diseases (disc degeneration, disc herniation, and spondylolisthesis) [56]. More than half of the studies reported a worse postoperative outcome in terms of pain, disability, health-related quality of life (HRQoL), and complications in women, while the remaining reported worse clinical outcomes in terms of satisfaction and HRQoL in male patients [56].…”
Section: Gender-related Differences After Major Vertebral Surgerymentioning
confidence: 99%
“…Salamanna et al analyzed in a review the studies considering sex-and gender-related differences in patients treated for lumbar degenerative diseases (disc degeneration, disc herniation, and spondylolisthesis) [56]. More than half of the studies reported a worse postoperative outcome in terms of pain, disability, health-related quality of life (HRQoL), and complications in women, while the remaining reported worse clinical outcomes in terms of satisfaction and HRQoL in male patients [56]. In studies examining pain, disability, and HRQoL differences between females and males, the complexity of evaluating these parameters, which include many clinical signs and subjective outcomes, must be considered [56].…”
Section: Gender-related Differences After Major Vertebral Surgerymentioning
confidence: 99%
“…None of the included studies analyzed sex differences because they did not test the efficacy of the patches in both sexes simultaneously; the research groups either used only male animals ( Ide and Tokunaga, 2018 ; Chen et al, 2020 ; Chen et al, 2022 ; de Lima Santos et al, 2020 ; He et al, 2021 ; Santos et al, 2022 ) or, to a lesser extent, female animals ( Thangarajah et al, 2018 ; Credille et al, 2023 ). It is now well established that sex differences, mainly due to hormonal variations and levels, affect musculoskeletal pathologies, including tendons ( Contartese et al, 2020 ; Tschon et al, 2021 ; Mondini Trissino Da Lodi et al, 2022 ; Salamanna et al, 2022 ; Salamanna et al, 2023 ). Clinical studies involving both men and women have shown a difference in prevalence ( Razmjou et al, 2016 ; Sabo et al, 2021 ) on the extent of shoulder pathology, repair, and healing, with a higher rate of re-tear in women than in men ( Collin et al, 2015 ; Razmjou et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%